Late Roman Pottery from the excavations of the archaic sanctuary - complex of Apollo in Despotiko Island, Cyclades. Preliminary results - Diamanti, Charikleia; Kourayos, Yannos; Lamprakis, Anastasios (Rei Cretariae Romanae Fautorum Acta, 2022)
Despotiko Island is very well known by the excavation of its Archaic sanctuary of Apollo of the 6th century BC. The study of the late Roman/early Byzantine settlement, which flourished upon the remains of the ancient sanctuary, started in the last two years. This paper presents the preliminary results of this research, based mainly on the pottery finds. These first observations, since the relative stratigraphic data is limited, are based mainly on diagnostic finds in order to define the main chronological range of the life of the settlement, as well as of the early Byzantine presence on the island in general. The pottery found in Despotiko, imported directly or indirectly via Paros, from known production centres such as North Africa, Asia Minor, Cyprus and the Aegean Sea littorals, indicates its well-established place on the Aegean Sea commercial routes. The Parian amphora material, which contributes to the study of the typology of this category, provides especially strong archaeological evidence into the direction of the connections of late Roman Despotiko, up to the last phase of its life, as a commercial outpost and a ‘satellite’ island of its ‘metropolitan’ neighbour early Byzantine Paros.